COVID-19 Pandemic in Portugal: Psychosocial and Health-Related Factors Associated with Psychological Discomfort - Pais-Ribeiro, José (2022)
: The COVID-19 pandemic is a stressful long-lasting event with an increasingly negative impact upon individuals. This study aimed at assessing the magnitude of depression, anxiety, and stress among adults living in Portugal during the first mandatory lockdown of 2020, and the psychosocial and health-related factors associated with these symptoms. A sample of 484 adults (73% women) with an average age of 40 years old (Standard Deviation, SD = 14.03) responded to an online survey. The survey included measures of depression, anxiety, stress, social support, COVID-19 interference in daily life, attitudes towards COVID-19, and health perception. The impact of the lockdown on psychological well-being was large, with up to 36% of the participants showing signs of at least mild psychological discomfort (i.e., depression, anxiety, and stress). Social support, COVID-19 interference on daily life, health perception, and age, explained all the dependent variables. Education level, income, attitudes towards COVID-19, and gender explained some of the dependent variables. These results suggest that the COVID-19 pandemic has a serious impact on the psychological health of Portuguese adults. The role of the procedures to control the pandemic on the mental health of Portuguese adults should not be underestimated.